(untitled) (Symposium on Life and Environmental Sciences, 2026)
This thesis examines pedagogical technologies for developing patriotism and civic duty in students through media content. In the digital era, media resources influence students’ worldview, values, social attitudes and understanding of national identity. Therefore, higher education institutions need purposeful methods for using media content not only as an informational tool, but also as a means of civic and patriotic education. The thesis emphasizes that patriotic and civic qualities can be developed effectively when media materials are selected according to educational goals, connected with national values, analyzed critically and transformed into reflective and socially useful student activity.